Konseling Individual Menggunakan Pendekatan Client Centered Therapy Untuk Meningkatkan Motivasi Belajar Siswa - Mirna Mirna; Muslim Afandi (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2022)
This study aims at analyzing (1) the imlementation of individual counseling therapy approac to increase students’ learning motivation. A descriptiveresearch methot was conductet involving one theacher counselor and the thee students of SMPN 3 Tambang. Intervew data collection on techniques were used and the narrative, After analyzing the data obtained in the field, it could be concluded that the students’ who derectly visited by teacher counselor and got direct guidance tended to be better behavior, the praktice of individual counseling using client centered therapy approach mostly be able to motivate the low-motivated lerners became better lerners, evalutionalisys was applied by the teacher counselor on the low  motivated students and the developed relevan communication whit other counseling parties, the  students whose lerning motivation was low  became more motivatedlernwrs after being treated with clien centered therapy approach,  a short term evaluation was cariied out in the order to know the client’s positive changes. The low attainment level of students’ lerning motivation was the major factor influencing the inplementation of guidance and counseling. In addition, there was a good relation between students’ and counselor in case of finding solution to overcome the low motivated learning students’ by using client centered therapy.